Witnessing the Unspeakable: On Testimony and Trauma in Svetlana Alexievich's The War’s Unwomanly Face and Zinky Boys - Lugarić Vukas, Danijela (Array, 2014)
Perhaps following Michel Foucault's notion from The History of Sexuality: An Introduction, where the French philosopher argues that Western societies became obsessed with the task of confessing and producing truth (which turned the Western man into „a confessing animal“), Shoshana Felman claims that „testimony [is] [...] the literary – or discursive – mode par excellence of our times, and [that] [...] our era can precisely be defined as the age of testimony“ [Felman, 1992, 5]. Defining it as a new form of literature, various scholars compare the genre of testimony with classical autobiographical and/or confessional forms of textuality and emphasize that testimonial literature significantly differs from previous textual forms in its appellative function. The unusually important role of the listener (or the witness of the testimonial speech act) rapidly alters the relationship between the subject (a witness) and the object (a listener) of a speech act. If we understand testimonial literature in a broader sense, i.e. as a form of textuality that refers to the abuse of human rights, violence and war, we could simultaneously consider it as a statement and as a declaration of the (un)speakability of a trauma. Considering the fact that literature in general and especially testimonial literature present a form of representation par excellence, while trauma illustrates exactly the opposite, i.e. a crisis in representation, testimonial literature is structured around extremely complex tensions between expressivity and speechlessness, the speakable and unspeakable and representative and non-representative. In that respect, the relationship between the subject (a witness) and the object (survivor’s recollections) of a speech act is distorted on another level. Traumatic experience is, namely, almost never represented in a form of a „simple memory“ [Caruth, 1995, 151]. Every testimonial act therefore inevitably faces the question of finding the adequate discursive medium for the transfer and articulation of that experience. That search often results in narrative strategies that are characterized by the fact that they govern the subject that pronounces them (as in the cases of uncontrolled/unwilling speech acts in cases when recollection of traumatic experience comes to its critical pinnacle). By means of a close reading of testimonial narratives by war survivors, collected by the Belarusian writer Svetlana Alexievich in her works The War’s Unwomanly Face (1985) and Zinky Boys (1991), my aim is to address and closely analyze the aforementioned tensions located inside the body of testimonial literature.